Modeling and Simulation of Moisture Transmission through Fibrous Structures Part II: Liquid Water Transmission (Journal of Fiber Bioengineering and Informatics, 2013)
Liquid flow through fibrous materials is important in a diverse range of applications. The prediction offlow through fibrous materials is influenced by a variety of factors and has been recognized as a favoritetopic of research in recent years. Capillary flow through fibrous materials takes place by two subsequentprocesses, known as wetting and wicking. Wetting of the material is the initial process, followed bywicking or flow through its capillaries. In high temperature and high humidity conditions, wickingthrough a textile fabric plays a very important role in maintaining the thermo-physiological comfort ofthe wearer by transferring the sweat from the skin to the outside surface of clothing. Prediction of themoisture transmission properties of fibrous materials is useful to characterize clothing comfort and ithelps in designing textile fabrics with specific requirements. A variety of mathematical models have beenproposed in order to understand the liquid flow characteristics of textile fabrics. Flow through capillarytubes and flow through porous structures have been the two main approaches taken by researchers inorder to model the capillary flow through fibrous structures. This paper reviews the relevant research inthe area of liquid moisture transmission through fibrous materials, followed by experimental verificationof some predictions using some of the developed equations. This experimental verification was undertakenby the authors.